Lithic technological responses to environmental change during the penultimate glacial cycle (MIS 7–6) at the Yangshang site, western Chinese Loess Plateau. (September 2021) - Zhao, Yuchao; Zhou, Jing; Chen, Fuyou; Wang, Xiaomin; Ge, Junyi; Gao, Xing; Stewart, Brian A.; Li, Feng
Abstract: A multidisciplinary fieldwork and research project was recently begun at the Yangshang site (220–140 ka), a late Early Paleolithic locale in the western Chinese Loess Plateau. 1696 lithic artifacts and 337 faunal remains were recovered during the excavation. Sedimentological and paleoenvironmental investigations indicate the site preserves a relatively long and minimally disturbed archaeological sequence associated with paleoenvironmental changes during MIS 7–6. A detailed techno-typological analysis of Yangshang's lithic assemblages was undertaken to examine the influence of glacial cycles on late Middle Pleistocene hominin technological strategies in the western Chinese Loess Plateau. The results show that while the Yangshang site is dominated by quartz-based core/flake assemblages typical of most Early Paleolithic sites in North China, the lithic assemblages provide evidence that different provisioning systems existed during the penultimate glaciation. We argue that these shifts reflect changes in land use and mobility that were tied to climate change. Our results suggest that theoretically informed statistical analyses of so-called unchanging and crude lithic technology can yield meaningful evidence for behavioral shifts.